A Study of Causal, Strategic, and Consequential Factors in Language Socialization for the Formation of Professional Identity among Language Teachers - Hadi , Somaye; Rezvani, Ehsan; Salehi, Hadi; Tabatabaei, Omid (Assessment and Practice in Educational Sciences, 2025)
This study aimed to investigate the causal, strategic, and consequential factors in language socialization that contribute to the formation of professional identity among language teachers, with a focus on uncovering how personal experiences, institutional conditions, and social interactions shape teachers’ professional selves. The research employed a qualitative, exploratory design based on grounded theory methodology. A total of 11 Iranian EFL teachers and teacher educators with a minimum of five years of professional experience were selected through purposive sampling to ensure diversity in gender, institutional background, and teaching context. Semi-structured interviews were conducted in Persian or English depending on participant preference, each lasting 45 to 75 minutes. The interview protocol, developed through literature review and expert validation, covered areas such as perceptions of professional identity, institutional influences, and intercultural experiences. Interviews were audio-recorded, transcribed verbatim, and analyzed through open, axial, and selective coding following Strauss and Corbin’s procedures to identify emerging patterns and construct a theoretical framework. The analysis revealed three major categories shaping teacher identity formation. Causal factors included educational experiences, personal characteristics, cultural values, and interactions with peers and colleagues. Strategic factors encompassed professional development activities, reflective practices, organizational support, and the integration of technology and networking opportunities. Consequential factors involved strengthened professional identity, improved teaching effectiveness, increased cultural adaptability, enhanced confidence, and higher job satisfaction, along with broader contributions such as promoting cultural diversity and social solidarity. These categories collectively highlighted the interdependent and cyclical nature of identity construction. The findings demonstrate that professional identity formation among language teachers is a dynamic and multidimensional process rooted in educational, social, and cultural experiences, operationalized through strategic actions, and leading to both personal and professional outcomes. Recognizing identity as a product of language socialization provides critical insights for teacher education, institutional policy, and professional development programs aimed at fostering resilient, adaptive, and sustainable teacher identities.